2022
DOI: 10.1344/der.2022.42.1-15
|View full text |Cite
|
Sign up to set email alerts
|

The use of ICT in Secondary Music Education and its relationship with teachers’ beliefs

Abstract: One of the most notable effects that COVID 19 has engendered in education is the ICT use in teaching at all educational levels. This study provides data on the ICT usage by teachers in the teaching of Music in Secondary Education in Andalusia (Spain). It also explores the relationship between ICT practices and teachers' perceptions of the educational value of ICT for teaching and learning. The empirical results obtained indicate that Secondary Education Music teachers use ICT in their teaching in a highly hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Third, some teachers reported high levels of self-efficacy in teaching with digital technology, even though they also believed they possessed low levels of skill in using digital technology (see 7.2.2). This contrasts with the trend observed in recent empirical literature that connects technical skills with beliefs, where the level of technical knowledge influences beliefs about digital technology and ultimately their usage (Eyles, 2018;Portero & Bravo, 2022;Zhang et al, 2021). Therefore, this study provides evidence that challenges the Will-Skill-Tool model (Knezek & Christensen, 2016) which proposes that will and skills can be separated.…”
Section: Music Education Is Infused With Digital Technologycontrasting
confidence: 98%
See 4 more Smart Citations
“…Third, some teachers reported high levels of self-efficacy in teaching with digital technology, even though they also believed they possessed low levels of skill in using digital technology (see 7.2.2). This contrasts with the trend observed in recent empirical literature that connects technical skills with beliefs, where the level of technical knowledge influences beliefs about digital technology and ultimately their usage (Eyles, 2018;Portero & Bravo, 2022;Zhang et al, 2021). Therefore, this study provides evidence that challenges the Will-Skill-Tool model (Knezek & Christensen, 2016) which proposes that will and skills can be separated.…”
Section: Music Education Is Infused With Digital Technologycontrasting
confidence: 98%
“…Other empirical research has found that teachers who lack confidence in their digital technology skills are less likely to use digital technology in their teaching practices (Tondeur et al, 2017;Wozney et al, 2006). A recent empirical study conducted in Spain, involving 153 teachers (a similar number to the sample cohort in this study), found that low levels of skill and knowledge were the likely reason for teachers' low levels of confidence and self-efficacy in using digital technology (Portero & Bravo, 2022). The general theme in the literature is that teachers' levels of skill, knowledge and self-efficacy in using digital technology influence how they use and experience digital technology in the classroom (Bowman, 2012;Lai & Hong, 2015;Scherer et al, 2019).…”
Section: Self-efficacymentioning
confidence: 60%
See 3 more Smart Citations